2014
DOI: 10.1007/s12288-014-0435-8
|View full text |Cite
|
Sign up to set email alerts
|

Time Dependent Release of Interleukin-8 and Tumor Necrosis Factor-α in Platelet Concentrate

Abstract: Contaminating white blood cells in stored platelet concentrate (PC) are the source of many pro-inflammatory cytokines. These are implicated in transfusion reactions. To study the release of interleukin (IL)-8 and tumor necrosis factor alpha (TNF-a) at different time interval in PC prepared byplatelet rich plasma (PRP) and buffy coat (BC) using different principles. Fifteen PCs were prepared by both the methods. The supernatants of PCs prepared by PRP and BC methods were collected aseptically after 1, 18, 65 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Shukla et al, found a relationship between the number of leucocytes and the TNF-α concentration (Shaiegan, 2006). The variation of TNF-α production in this study is due to the different number of leucocytes left in the TC component, but in this study, the number of leucocytes per bag was not measured (Shukla et al, 2014).…”
Section: Results Of Tnf-α Concentration Differential Testmentioning
confidence: 75%
“…Shukla et al, found a relationship between the number of leucocytes and the TNF-α concentration (Shaiegan, 2006). The variation of TNF-α production in this study is due to the different number of leucocytes left in the TC component, but in this study, the number of leucocytes per bag was not measured (Shukla et al, 2014).…”
Section: Results Of Tnf-α Concentration Differential Testmentioning
confidence: 75%